2020
DOI: 10.1371/journal.pone.0240573
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of software methods for estimating protein-protein relative binding affinities

Abstract: A growing number of computational tools have been developed to accurately and rapidly predict the impact of amino acid mutations on protein-protein relative binding affinities. Such tools have many applications, for example, designing new drugs and studying evolutionary mechanisms. In the search for accuracy, many of these methods employ expensive yet rigorous molecular dynamics simulations. By contrast, non-rigorous methods use less exhaustive statistical mechanics, allowing for more efficient calculations. H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 98 publications
1
26
0
Order By: Relevance
“…This approach is comparable to other knowledge-based structural methods such as Dcomplex which is based on distance-specific contact potentials trained on the monomer structures. By combining structural and evolutionary profile analyses derived from the binding interfaces, the BindProfX approach showed potential for improvements over both the statistics-based and physics-based FoldX potentials. The BeAtMuSiC approach adapted in our study that was further enhanced through ensemble-based averaging of binding energy computations yielded a good correlation between prediction and experiments and was successfully used for the binding free analysis of the SARS-CoV-2 S binding with the host receptor and antibodies. The recent analysis of computational tools for estimating protein–protein binding probed several approaches or their predictive ability of relative binding affinities for 654 single mutations on antibody–antigen and nonantibody–antigen complexes . Instructively, this analysis showed context-dependent and system-dependent strengths and weaknesses of these tools.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…This approach is comparable to other knowledge-based structural methods such as Dcomplex which is based on distance-specific contact potentials trained on the monomer structures. By combining structural and evolutionary profile analyses derived from the binding interfaces, the BindProfX approach showed potential for improvements over both the statistics-based and physics-based FoldX potentials. The BeAtMuSiC approach adapted in our study that was further enhanced through ensemble-based averaging of binding energy computations yielded a good correlation between prediction and experiments and was successfully used for the binding free analysis of the SARS-CoV-2 S binding with the host receptor and antibodies. The recent analysis of computational tools for estimating protein–protein binding probed several approaches or their predictive ability of relative binding affinities for 654 single mutations on antibody–antigen and nonantibody–antigen complexes . Instructively, this analysis showed context-dependent and system-dependent strengths and weaknesses of these tools.…”
Section: Resultsmentioning
confidence: 94%
“…Instructively, this analysis showed context-dependent and system-dependent strengths and weaknesses of these tools. Moreover, physics-based methods often display a similar predictive power to comparable but much faster knowledge-based methods which are indispensable for massive mutational scanning experiments . Importantly, it was concluded that most methods can quickly and accurately differentiate between favorable and unfavorable mutations rather than accurately predicting the actual binding affinities …”
Section: Resultsmentioning
confidence: 99%
“…Although this modeling approach remarkably identified six MARMs, there is still a need for better modeling strategies to improve correlation between experimental and predicted ΔΔ G Bind values for antigen-mAb complexes. Use of MD simulation to provide conformation sampling is the key reason behind the performance of the MD+FoldX approach (56). However, empirical validation of the MD+FoldX approach carried out in this study further emphasizes the need for improved conformational strategies for large protein-protein complexes.…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy between modeling and empirical data is likely due to the water-mediated interaction of T1416 with CA residues R173 and E63 (21). These modeling inaccuracies are expected because one of the significant limitations of fast protein-protein binding affinity prediction tools (FoldX and PyRosetta) is that they ignore the explicit presence of bridging water molecules (31).…”
Section: Discussionmentioning
confidence: 99%